2020
DOI: 10.1002/ange.202009258
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Reactivity of a Heterogeneous Catalyst using N‐Heterocyclic Carbene Ligands for C−H Activation Reactions

Abstract: We report the dramatic impact of the addition of N‐heterocyclic carbenes (NHCs) on the reactivity and selectivity of heterogeneous Ru catalysts in the context of C−H activation reactions. Using a simple and robust method, we prepared a series of new air‐stable catalysts starting from commercially available Ru on carbon (Ru/C) and differently substituted NHCs. Associated with C−H deuteration processes, depending on Ru/C‐NHC ratios, the chemical outcome can be controlled to a large extent. Indeed, tuning the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…28 Pieters et al also controlled the selectivity of Ru NPs supported on carbon in the isotopic H/D exchange by modifying the surface metal with NHCs. 29 However, the surface modification of supported MNPs with NHCs not only may improve their selectivity, but also is able to increase their stability. Recently, it has been shown that NHCs bearing a pyrene group can enhance the stability of graphenesupported MNPs via non-covalent π-interactions between the pyrene tag and the graphene layer.…”
Section: Introductionmentioning
confidence: 99%
“…28 Pieters et al also controlled the selectivity of Ru NPs supported on carbon in the isotopic H/D exchange by modifying the surface metal with NHCs. 29 However, the surface modification of supported MNPs with NHCs not only may improve their selectivity, but also is able to increase their stability. Recently, it has been shown that NHCs bearing a pyrene group can enhance the stability of graphenesupported MNPs via non-covalent π-interactions between the pyrene tag and the graphene layer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, under the same catalytic conditions (0.1 mol% Pt, H 2 O, 5 bar H 2 , 25 °C, 5 h) the monometallic catalyst Pt@rGO presented a conversion of 82.9% and a slightly lower selectivity to the corresponding alcohol (8), due to the formation of a small amount of the HDO product, 2-methoxy-4-methylphenol (9) (see Table 1, entries 5 and 6). In the hydrogenation of levoglucosenone (10) with Pt@rGO/Sn 0.8 we observed complete conversion in 5 hours, and a selectivity of 58% towards the fully hydrogenated product, levulinyl alcohol (12) (see Table 1, entry 7). However, at the same reaction time, Pt@rGO showed a slower conversion (91.2%) and 92% selectivity to the product (11), due to its lower reactivity in the hydrogenation of CvO bonds compared to the functionalized catalyst (see Table 1, entry 8).…”
Section: Catalytic Studiesmentioning
confidence: 91%
“… 15 More recently, water-soluble Ru NPs stabilized by sulfonated NHC ligands were also reported in the H/D exchange of l -lysine. 16 These catalytic systems allowed an efficient and selective late-stage H/D exchange in complex molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Following the same methodology, the enantiospecific deuterium incorporation at the stereogenic center of amino acids was also achieved . More recently, water-soluble Ru NPs stabilized by sulfonated NHC ligands were also reported in the H/D exchange of l -lysine . These catalytic systems allowed an efficient and selective late-stage H/D exchange in complex molecules.…”
Section: Introductionmentioning
confidence: 99%